Characterization of an Omega-3 Desaturase From Phytophthora parasitica and Application for Eicosapentaenoic Acid Production in Mortierella alpina - Tang, Xin; Chen, Haiqin; Mei, Tiantian; Ge, Chengfeng; Gu, Zhennan; Zhang, Hao; Chen, Yong Q.; Chen, Wei (Frontiers in Microbiology, 2018)
Omega-3 long-chain polyunsaturated fatty acids (LC-PUFAs) have important therapeutic and nutritional benefits in humans. In the biosynthesis pathways of these LC-PUFAs, omega-3 desaturase plays a critical role. In this study, we report a new omega-3 desaturase (PPD17) from Phytophthora parasitica. This desaturase shares high similarities with the known omega-3 desaturases and was expressed in Saccharomyces cerevisiae for the activity and substrate specificity research. The desaturase has a wide omega-6 fatty acid substrate, containing both 18C and 20C fatty acids, and exhibits a strong activity of delta-17 desaturase but a weak activity of delta-15 desaturase. The new desaturase converted the omega-6 arachidonic acid (AA, C20:4) to EPA (an omega-3 LC-PUFA, C20:5) with a substrate conversion rate of 70%. To obtain a high EPA-producing strain, we transformed PPD17 into Mortierella alpina, an AA-producing filamentous fungus. The EPA content of the total fatty acids in reconstruction strains reached 31.5% and was followed by the fermentation optimisation of the EPA yield of up to 1.9 g/L. This research characterized a new omega-3 desaturase and provides a possibility of industrially producing EPA using M. alpina.